A Compact Wideband Solar-Cell Integrated Antenna - Ali, Ahmed; Park, Ikmo (2022 International Symposium on Antennas and Propagation, ISAP 2022, 2022)
This paper describes a wideband and ultra-low profile solar-cell integrated antenna with a high form factor. An indium gallium selenide-based solar cell is utilized to make the built-in solar-cell antenna, which is designed to operate from the solar cell using a slot that is carved into it. The proposed design has an ultra-low profile structure of 0.0056 λ0 at 2.96 GHz with overall dimensions of 50 mm × 27 mm × 0.571 mm (0.49λ0 × 0.26 λ0× 0.0056λ0 at 2.96 GHz). Moreover, the presented design has a-10dB impedance bandwidth of 43.24%, a maximum gain of 2.45 dBi, a form factor of 99.33%, and optical transparency of 100%.
Keywords: Cell-be; Cell/B.E; Cell/BE; Form factors; Integrated antennas; Low-profile; Solar cell integrated antenna; Ultra low profile antennas; Wide-band; Wideband antenna; solar cell integrated antenna; ultra-low profile antenna; wideband antenna